Liquidity and Market Efficiency – Alive and well? - Peter Fisher; Petri Jylhä; Jussi Keppo; Erkki Liikanen; George G. Pennacchi (SUERF - The European Money and Finance Forum, 2015)
The present SUERF Study includes a selection of papers based on the authors' contributions to the Helsinki conference, jointly organized by SUERF,and Bank of Finland on 3 July,2015.
Keywords: E43; E44; E51; E52; E58; F32; F34; F36; G14; G28; 330